Short-term increase in the carriage of azithromycin-resistant Escherichia coli and Klebsiella pneumoniae in mothers and their newborns following intra-partum azithromycin: a post hoc analysis of a double-blind randomized trial. Issue 1 (27th January 2021) - Getanda, Pauline; Bojang, Abdoulie; Camara, Bully; Jagne-Cox, Isatou; Usuf, Effua; Howden, Benjamin P; D'Alessandro, Umberto; Bottomley, Christian; Roca, Anna
Abstract: Objectives: To evaluate the impact of one oral dose of intrapartum azithromycin (2 g) on the carriage and antibiotic resistance of Escherichia coli and Klebsiella pneumoniae in the nasopharynx, breast milk and vaginal swabs of mothers and K. pneumoniae in the nasopharynx of their newborns. Methods: We performed a post hoc analysis of a double-blind, placebo-controlled randomized-trial (ratio 1:1) conducted in The Gambia. Breast milk (BM) and vaginal swabs (VS) from mothers and nasopharyngeal swabs (NPS) from mother–newborn pairs were collected at different timepoints during the 4 week follow-up. Samples were processed using standard microbiological procedures. For BM and NPS post-intervention results were combined for analysis. Results: In the original trial 829 mothers were randomized. In this analysis, complete sample sets were available for 630 mothers for E. coli analysis (76.0%) and 564 mother–newborn pairs for K. pneumoniae analysis (68.0%). For E. coli, carriage prevalence in BM and VS was similar in both arms but resistance was higher in the azithromycin arm in VS (2.6% versus 0%, P =  0.004). For K. pneumoniae, carriage prevalence was higher in the azithromycin arm for BM (13.8% versus 8.7%, P =  0.055) but not for VS or NPS. Prevalence of azithromycin resistant K. pneumoniae was higher in the azithromycin arm for BM (3.6% versus 1.0%, P =  0.050) and VS (1.5% versus 0% P =  0.057). Conclusions: Oral intrapartum azithromycin did not reduce carriage of E. coli and K. pneumoniae and was associated with an increase in the prevalence of azithromycin-resistant E. coli and K. pneumoniae isolates in BM and VS.